2019
DOI: 10.3389/fendo.2019.00737
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Direct 131I Therapy After Detection of Biochemical Recurrence in Intermediate or High-Risk Differentiated Thyroid Cancer: A Retrospective Cohort Study

Abstract: Background: Patients treated for intermediate- or high-risk differentiated thyroid carcinoma (DTC) and Thyroglobulin (TG) elevation during follow-up, require a diagnostic whole-body scan (DWBS) and if positive, 131I treatment. This approach can lead to a delay in treatment and increased costs. The purpose of this study is to compare the oncologic outcomes associated to administration of direct therapy with 131I at first biochemical recurrence.Methods: Retrospective cohort study of patients with intermediate- o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…In other patients, the symptoms could lead to chronic radiation sialadenitis. These complications are clinically significant in 10–30% of subjects even if their frequency is not well known [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. In particular, in the prospective cohort study by Hyer et al, patients were treated with an ablative activity of 3GBq and a further of 5.5 GBq in case of residual disease.…”
Section: Collateral Effects Of 131 I Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In other patients, the symptoms could lead to chronic radiation sialadenitis. These complications are clinically significant in 10–30% of subjects even if their frequency is not well known [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. In particular, in the prospective cohort study by Hyer et al, patients were treated with an ablative activity of 3GBq and a further of 5.5 GBq in case of residual disease.…”
Section: Collateral Effects Of 131 I Therapymentioning
confidence: 99%
“…Today, thyroid cancer is presented at an earlier stage and has a lower recurrence rate of 3–10% [ 51 , 52 , 53 , 54 ]. Moreover, Carrillo et al demonstrated that patients with DTC treated with 131 I, which have a biochemical recurrence and no diagnostic WBS (DWBS) or extensive studies, have lower frequencies of second recurrence (SR) compared to the group that, prior RAIT, underwent a DWBS with 5 mCi of 131 I and Magnetic Resonance Imaging (MRI) and/or 18F-FDG PET if DWBS was negative [ 55 ]. In a study by Rubino et al, second primary malignancies (SPM) and leukemia risk were evaluated.…”
Section: Collateral Effects Of 131 I Therapymentioning
confidence: 99%
“…Radioiodine therapy (1.85–7.40 GBq) is performed if radioiodine-avid lesions are identified. However, diagnostic whole-body scans are limited, e.g., by a low diagnostic accuracy of 36% in biochemical recurrent intermediate- or high-risk DTC patients [ 5 ]. A suitable alternative is iodine-124 ( 124 I) positron emission tomography (PET) imaging.…”
Section: Introductionmentioning
confidence: 99%